Time changing effects of external shocks on macroeconomic fluctuations in Peru: empirical application using regime-switching VAR models with stochastic volatility - Rodríguez, Gabriel (2022)
This article quantifies and analyzes the evolving impact of external shocks on Peru’s macroeconomic fluctuations in 1994Q1-2019Q4. For this purpose, we use a group of models with regimeswitching time-varying parameters and stochastic volatility (RS-VAR-SV), as proposed by Chan and Eisenstat (2018). The data suggest a model with contemporaneous coefficients and constant lags and intercepts, but with regime-switching variances; and point to the existence of two regimes. The IRFs, FEVDs, and HDs show that: (i) China growth shocks have a higher impact on Peru’s output growth (around 0.8%); (ii) financial shocks contract domestic output growth by 0.3% and domestic monetary policy is synchronized with Fed rate movements; (iii) external shocks explain 35% and 70% of output fluctuations under regimes 1 and 2, respectively; and (iv) China growth shocks contributed 1.0 p.p. to the 1.1-p.p. increase (around 89%) in Peru’s output growth between regimes 1 and 2. Additionally, we validate these results by performing seven robustness exercises consisting in changing priors, reordering variables, changing variables, and using four different specications for the baseline model.